Corporate Governance Implementation on Corporate Value in Indonesia and Malaysia Sharia Banks - Nurul, Mochammad; Alief, Jeffits Khusnu; Subekti , Gemelthree Ardhiatus (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2025)
Islamic banking has experienced rapid growth in Southeast Asia. Islamic Social Reporting (ISR) integrates Islamic values to demonstrate banks' compliance with religious standards. This study analyzes ISR disclosure's mediating role between corporate governance mechanisms and firm value in Islamic banking. Using panel data from 2014-2020 from 12 Indonesian and 15 Malaysian Islamic banks (168 company-year observations), we employ ordinary regression analysis to analyze how board size, board independence, Sharia supervisory board size, audit committee size, and audit committee meeting frequency affect corporate value through ISR disclosure. Board size and independence significantly affect firm value, with ISR as partial mediator, showing these mechanisms enhance value through stakeholder trust. The Sharia supervisory board size impacts both ISR disclosure and firm value, with ISR partially mediating, indicating effective oversight enhances value through direct supervision and ethical reporting. The audit committee size and meeting frequency increase ISR disclosure, with ISR fully mediating their relationship with firm value, suggesting audit committees influence value through improved social reporting rather than direct market effects. These results show governance mechanisms operate differently requiring tailored strategies to optimize social responsibility and financial performance.